Crystallinity-dependence of ionic conductivity in the ion pairs of a multi-interactive anion. Issue 20 (16th February 2016) - Lee, Gil Ryeong; Ohtsu, Hiroyoshi; Koo, Jinyoung; Yakiyama, Yumi; Park, Moon Jeong; Inoue, Daishi; Hashizume, Daisuke; Kawano, Masaki
Abstract : Sodium and ammonium salts of a multi-interactive molecule possessed different main-structural units, which explains their ion conductivities and stabilities against water. Abstract : Ammonium and sodium salts (ion pairs) of a multi-interactive tri(4-pyridyl)hexaazaphenalenyl anion (TPHAP − ) showed completely different ion-conductive properties depending on the crystal structure. TPHAP columnar crystals showed a high conductivity of 10 −3 S cm −1 while retaining their structures even under humid conditions, whereas TPHAP dimer crystals exhibited a conductivity of ∼10 −5 S cm −1 with crystallinity deterioration. The main unit structures induced by multi-interactivity realized different water accessibility, which explains the differences in their ion conductivity and stability against humidity.